Computer modelling of the thermal decomposition of solids - De la Croix, Annemarie (Rhodes University, Faculty of Science, Department of Chemistry, 1996)
Decompositions of solids are typically of the form: A(s) ----> B(s) + gases. Symmetry-controlled routes (based on known and hypothetical crystal structures) for transforming the solid reactant into the solid product were devised as possible decomposition pathways. Lattice energies of the reactants, of the postulated transient intermediate structures and of the final solid products were then estimated by crystal modelling procedures. Profiles of lattice energy changes during the proposed decomposition routes were constructed and any energy barriers were compared with experimental activation energies reported for the thermal decompositions. The crystal modelling was performed with the computer program WMIN. Calculation of the lattice energies involved the development of a model potential for the perfect lattice and the evaluation of the interatomic parameters. The potential was based on the Born model of ionic solids using the Buckingham potential (Ã˜(r)= Aeâ »r/p - C/râ ¶) to describe the short-range energy contribution. Empirical fitting was used to establish reliable interatomic energy parameters. The reliability of the interatomic potentials was assessed by calculating crystal structures and lattice energies (which were not included in the fitting). The particular reactions selected for modelling were the decompositions of the alkaline-earth metal (Ca, Sr, Ba) peroxides and carbonates: M0â‚‚(s) ---> MO(s) + Â¹/â‚‚0â‚‚(g) MC0â‚ƒ(s) ---> MO(s) + COâ‚‚(g)The lattice energies calculated for the known structures were in good agreement with reported values, (except for Ba0â‚‚ and BaC0â‚ƒ) which provided support for the adequacy of the potential model used. Activation energies calculated for the decomposition of the carbonates were in the correct order but hlgher than experimental values, i. e., 422, 422, 465 and 499 kJ molÌ„Ì„â »Â¹ compared to the experimental values of 205, 87(?), 222 and 283 kJ molÌ„Ì„â »Â¹ for CaC0â‚ƒ (calcite), CaC0â‚ƒ(aragonite), SrC0â‚ƒ and BaC0â‚ƒ. The values calculated for the peroxides (91 and 100 kJ molâ »Â¹ compared to the experimental values of 119 and 185 kJ molâ »Â¹ for Sr0â‚‚ and Ba0â‚‚ respectively) were less satisfactory but could be a reflection of the poor structural data used for the peroxides. The significance of this approach to the modelling of solid decompositions is discussed.
Keywords: Solids -- Thermal properties -- Computer simulation